Fibromyalgia syndrome and related factors in hemodialysis, peritoneal dialysis, and renal transplant patients: A cross-sectional study - Ayla Çağlıyan Türk,; Sultan Özkurt,; İbrahim Doğan,; Füsun Şahin, (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the point prevalence of fibromyalgia in patients on hemodialysis and peritoneal dialysis and after renal transplantation compared to healthy controls and to evaluate depressive symptoms, anxiety level, and the impact of fibromyalgia on quality of life (QoL). Patients and methods: Between January 2018 and January 2019, a total of 107 hemodialysis patients (Group 1) (48 males, 59 females; median age: 50 years; range, 42 to 56 years), 51 peritoneal dialysis patients (Group 2) (32 males, 19 females; median age: 49 years; range, 39 to 54 years), 52 renal transplant patients (Group 3) (23 males, 29 females; median age: 45.5 years; range, 37 to 52 years), and 50 healthy controls (Group 4) (23 males, 27 females; median age: 46.5 years; range, 42 to 50 years) were included in the study. Age, sex, amount of time spent on dialysis, and laboratory data were recorded. Impact of fibromyalgia on QoL was evaluated using the Fibromyalgia Impact Questionnaire (FIQ), while depressive symptoms and anxiety level were assessed using the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI), respectively. Results: The point prevalence of fibromyalgia was 14% in Group 1 (n=15), 5.9% in Group 2 (n=3), 9.6% in Group 3 (n=5), and 4% in Group 4. There was a significant difference in the point prevalence of fibromyalgia between the hemodialysis group and healthy controls (p<0.05). The median FIQ scores were significantly higher in all patient groups than Group 4 (p<0.001); however, there was no significant difference between the patient groups (p>0.05). The median BDI scores were significantly higher in Group 1 and Group 2 than Group 4 (p<0.05). The median BAI scores were significantly higher in Group 1 than Group 4 (p<0.05). When the patients with and without fibromyalgia were compared, FIQ and BAI in Group 1, BAI in Group 2, and FIQ in Group 3 significantly differed (p<0.05). There was no relationship between fibromyalgia and any of the laboratory data, age, or time spent on dialysis (p>0.05). Conclusion: Fibromyalgia is significantly more common among hemodialysis patients than healthy individuals with a similar prevalence to the healthy individuals for peritoneal dialysis and renal transplant patients. The presence of fibromyalgia is related to depressive symptoms, anxiety, and higher impact on QoL for patients with chronic kidney disease.